Analytical modeling of groundwater contamination under uncertainty - He, Yujun (2014)
Groundwater contamination is considered to be one of the most significant ecological and health problems. The contaminant released from the source will move down-gradient of the groundwater flow and greatly affects the general environmental features of large regions and drinking water supply conditions in many countries (U.S. Environmental Protection Agency 1987).